Facile synthesis of novel blue light and large Stoke shift emitting tetradentate polyazines based on imidazo[1, 5-a]pyridine – Part 2. (August 2017) - Volpi, G.; Garino, C.; Priola, E.; Diana, E.; Gobetto, R.; Buscaino, R.; Viscardi, G.; Barolo, C.
Abstract: A series of new imidazo[1, 5- a ]pyridines was obtained through a facile multiple condensation procedure, involving the reaction of two methanamine and several largely available and inexpensive di- and tricarboxylic acids. Such poliazine products show different and tuneable coordination motifs suitable for mono-, di-, and tritopic coordination sites. Furthermore they display interesting optical properties: tuneable luminescence, significant quantum yields, large Stokes' shifts and strong halochromic effects, enabling their technological application. Graphical abstract: Highlights: New multiazine fluorophores obtained through a facile multiple cyclization. Two ortho substituted bis-imidazo[1, 5- a ]pyridines synthesized for the first time. Tuneable emissions, high ϕ, large Stokes' shifts, strong halochromic effects. Optical properties suitable for technological applications (DSCs, LECs, NLO). Extension of the previously reported class of multiazine ligand derivatives.